2014
DOI: 10.1063/1.4886336
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-grained modeling of DNA oligomer hybridization: Length, sequence, and salt effects

Abstract: A recently published coarse-grained DNA model [D. M. Hinckley, G. S. Freeman, J. K. Whitmer, and J. J. de Pablo, J. Chem. Phys. 139, 144903 (2013)] is used to study the hybridization mechanism of DNA oligomers. Forward flux sampling is used to construct ensembles of reactive trajectories from which the effects of sequence, length, and ionic strength are revealed. Heterogeneous sequences are observed to hybridize via the canonical zippering mechanism. In contrast, homogeneous sequences hybridize through a slith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
89
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 60 publications
7
89
1
Order By: Relevance
“…The observed relationship between the length and the WGM shift for the DNA pairs varying from 11-mer to 15-mer, suggests an unpredicted behavior and agrees with the aforementioned study. 39 Although the fact that it is challenging to interpret the data when all the factors considered together, we believe that, the increased pair length can lead to slow target binding kinetics on the biosensor surface by allowing relatively slower target penetration 40 and decrease the number of stable DNA duplexes, thus causing smaller WGM shifts. Another possible effect that can reduce the overall target-probe binding ratio, which is already smaller than unity (0.84) for 11-mer DNA pair, is the repulsive forces between the negatively charged surface and the target ss-DNA.…”
Section: Analytical Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The observed relationship between the length and the WGM shift for the DNA pairs varying from 11-mer to 15-mer, suggests an unpredicted behavior and agrees with the aforementioned study. 39 Although the fact that it is challenging to interpret the data when all the factors considered together, we believe that, the increased pair length can lead to slow target binding kinetics on the biosensor surface by allowing relatively slower target penetration 40 and decrease the number of stable DNA duplexes, thus causing smaller WGM shifts. Another possible effect that can reduce the overall target-probe binding ratio, which is already smaller than unity (0.84) for 11-mer DNA pair, is the repulsive forces between the negatively charged surface and the target ss-DNA.…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…As described formerly, target binding kinetics to the surface attached probes depends on many factors such as DNA strand sequence, 39 probe/target length, 40 the rate of target diffusion from bulk, 41 surface coverage of the attached probes, 42 reachability of nucleation sites, and even complementary segment location (complementary to upper or nucleation sitenear portion of the probe). 12 Hinckley et al 39 reported theoretically that short (<30 mer), heteregenous DNA sequences did not show consistent trends in terms of hybridization binding rate constants, and the rate constant slightly decreased as the base number increased from 10-mer to 15-mer. Also, it had been observed in another study 43 that increased length decreased the hybridization rate.…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…Most of the successful CG models use from 2 (oxDNA [135][136][137][138], and Aksim nti v's m d l [148]), or 3 (3SPN [131][132][133]139,140], BioModi [149]), to eight beads per nucleotide (see Figure 2, and Table 1 for more details). However, coarser models with five beads per base-pair step (four nucleotides), or even a single bead per nucleotide have emerged [126,127].…”
Section: Coarse-grain Studiesmentioning
confidence: 99%
“…In this regard, several coarse-grained models were applied to understand certain processes of biological interest, like duplex formation starting from short ssDNA oligomers [127,131,132,142]. Other models have shown to be useful in reproducing the structure of DNA/RNA duplexes [129], or structural properties such as the sequencedependent/salt-dependent persistence length [127,131,132], or the DNA curvature. The model from Vercauteren and coworkers was able to reproduce the topology of several DNA mini-circles with different link numbers, simulated using explicit K + Cl -ions [126].…”
Section: Coarse-grain Studiesmentioning
confidence: 99%
“…A wide range of CG models already exist for DNA [27][28][29][30][31][32][33][34][35][36][37], but here we keep the DNA molecule at AT resolution embedded in a multiresolution supramolecular bundled-SPC/MARTINI univalent salt solution. The simulation setup is similar to the one we used in our previous multiscale simulation of the dielectric properties of the solvated DNA molecule [38].…”
mentioning
confidence: 99%